Capacity of Albit® Plant Growth Stimulator for Mitigating Side-effects of Pesticides on Soil Microbial Respiration - Neaman, Alexander; Yanushevskaya, Eleonora B.; Mikhailova, Yelena V.; Mondaca, Pedro; Neaman, Alexander (JNRD - Journal of Natural Resources and Development, 2017)
Microorganisms give an early and integrated measure of soil functioning. In particular, soil microbial respiration is recommended for monitoring soil quality. The present study aims to determine the capacity of Albit® (poly-β-hydroxybutyrate, PHB) to reduce the detrimental effects of pesticides on soil microbial respiration. The effects of three conventional pesticides (deltamethrin, dithianon, and difenoconazole) on basal respiration (BR) and substrate-induced respiration (SIR) were assessed in the presence and absence of Albit®. The studied pesticides caused negative impacts on soil functioning, reducing BR and SIR. Applications of Albit® increased BR and SIR, and both BR and SIR were kept similar to the control when pesticides were applied with Albit®. PHB, an active ingredient of Albit®, is known to increase beneficial microflora in the rhizosphere due to its regulatory activity on indigenous microorganisms. Thus, more studies should be carried out under different edaphoclimatic conditions to study the benefits of Albit® applications along with pesticides in order to mitigate their side effects on soil microbial functioning.